2021
DOI: 10.1177/03611981211049147
|View full text |Cite
|
Sign up to set email alerts
|

Safety Impact of Connected Vehicles on Driver Behavior in Rural Work Zones under Foggy Weather Conditions

Abstract: Work zone safety is one of the paramount goals of the safety community. Safety in WZs is a particular concern under foggy conditions as they represent an exogenous factor contributing to high variability in driver behavior. In line with the Connected Vehicle (CV) Pilot Deployment Program on Interstate-80 (I-80) in Wyoming, this study investigates the safety benefits of CV Work Zone Warning (WZW) applications on driver behavior during foggy weather conditions. A work zone (WZ) was simulated using VISSIM in four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Utilizing the fuzzy comprehensive evaluation method, a set of evaluative comments was established, and a single-factor evaluation fuzzy matrix was constructed. The entropy weighting method was then employed to ascertain the weight of factors to be assessed, resulting in a comprehensive evaluation [ 11 ]. Conversely, Agushaka et al (2022) proposed the Mongoose Optimization Algorithm, a novel meta-heuristic algorithm aimed at solving classical and CEC 2020 benchmark functions and 12 continuous/discrete engineering optimization problems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Utilizing the fuzzy comprehensive evaluation method, a set of evaluative comments was established, and a single-factor evaluation fuzzy matrix was constructed. The entropy weighting method was then employed to ascertain the weight of factors to be assessed, resulting in a comprehensive evaluation [ 11 ]. Conversely, Agushaka et al (2022) proposed the Mongoose Optimization Algorithm, a novel meta-heuristic algorithm aimed at solving classical and CEC 2020 benchmark functions and 12 continuous/discrete engineering optimization problems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Our review found that DRAC does not consider the response time (RT) of the following vehicle. Adomah et al suggest a modified DRAC (MDRAC) as an improvement over regular DRAC [37]. The key distinction between DRAC and MDRAC is that the latter considers the response time of the following vehicle.…”
Section: ) Individual Ssmsmentioning
confidence: 99%
“…(Bussey 2019). But there is limited research on impacts of retrofitting current roadworks set-ups in scenarios that include CATs, with the relatively few existing publications being based on heterogenous vehicle operations, rather than segregated CAT lane configuration (Liu, Tight et al 2019, Abdulsattar, Mostafizi et al 2020, Adomah, Khoda Bakhshi et al 2021, Pourfalatoun and Miller 2021.…”
Section: Motivation For Studymentioning
confidence: 99%
“…Previous research on CAVs and work zones showed how autonomous vehicles can improve on safety and traffic flows (Adomah, Khoda Bakhshi et al 2021). But, this only considered heterogenous traffic.…”
Section: Literature Reviewmentioning
confidence: 99%